Pharmacokinetics and Safety of the Nucleoside Analog Antiviral Drug Galidesivir Administered to Healthy Adult Subjects. Issue 4 (19th February 2022) - Mathis, Amanda; Collins, David; Dobo, Sylvia; Walling, Dennis M.; Sheridan, William P.; Taylor, Ray
Abstract: Galidesivir (BCX4430) is an adenosine nucleoside analog broadly active in cell culture against multiple RNA virus families, and active in animal models of viral diseases associated with Ebola, Marburg, yellow fever, Zika, and Rift Valley fever. Current studies demonstrated the pharmacokinetics and safety of the first‐in‐human evaluations of galidesivir as intramuscular (IM) and intravenous (IV) formulations. Two double‐blind, placebo‐controlled, dose‐ranging studies were conducted enrolling 126 healthy subjects. Study 1 evaluated the safety and tolerability of IM galidesivir over single day dosing, single day dosing ± lidocaine, and 7‐day dosing with lidocaine. Study 2 evaluated the safety and tolerability of single ascending doses of IV galidesivir. Safety and tolerability were evaluated via clinical and laboratory monitoring. The plasma concentration–time profile of galidesivir at doses 0.3 to 10 mg/kg IM was characterized by rapid absorption, an initial rapid distribution and clearance phase, and an extended terminal elimination phase. The initial rapid distribution and extended terminal elimination were mimicked in the profile of galidesivir at doses 5 to 20 mg/kg IV. No fatal events or related serious adverse events were reported. No clinically significant dose‐related trends in laboratory values, vital signs, electrocardiograms, or echocardiograms were noted. Galidesivir was safe and generally well tolerated.